Stability of pesticide in water emulsion induced by mixed surfactants - Liu, Jiexiang; Qian, Cuihua; Zhang, Xiaoguang (Tenside Surfactants Detergents, 2022)
Etofenprox emulsions in water were prepared by mixing polyoxyethylene (20) castor oil ether (EL-20) with the surfactants polyoxyethylene (10) octylphenyl ether (OP10), polyoxyethylene styrenated phenol ether (602), polyoxyethylene (40) castor oil ether (EL-40) and octylphenyl polyoxyethylene phosphonate (OPP), respectively. Emulsion stability was investigated and analysed based on the hydrophilic-lipophilic equilibrium, surfactant structure and surface tension of the diluted emulsion. The results showed that the emulsions (EL-40 + EL-20) and (OPP + EL-20) had relatively high stability. Subsequently, the surfactants polyoxyethylene-polyoxypropylene-styrenated phenol ether (1601), polyalkoxylated butyl ether (LQ) and OPP were added separately to the emulsions (EL-40 + EL-20), (602 + EL-20) or (OPP + EL-20) to obtain the ternary surfactant systems. Emulsion stability was further investigated and discussed based on droplet size, zeta potential and surface tension. The results revealed that the addition of OPP and LQ could further improve the stability of (EL-40 + EL-20) emulsions, and that LQ was also beneficial for the stability of (OPP + EL-20) emulsions. The stability mechanism of the emulsion was also discussed.